2022
DOI: 10.1213/ane.0000000000005916
|View full text |Cite
|
Sign up to set email alerts
|

The Perioperative Human Digital Twin

Abstract: GLOSSARY BRCA = BReast CAncer gene; ECG = electrocardiogram; EHR = electronic health record; EMR = electronic medical record; GPS = Global Positioning System; HDT = human digital twin; HER-2 = human epidermal growth factor receptor 2; HIPAA = Health Insurance Portability and Accountability Act; IoMT = Internet of Medical Things; IoT = Internet of Things; PGHD = person-generated health data; PWC = physiologic data warehouse; RPM = remote patient monitoring; SARS-CoV-2 = severe acute respiratory syndrome coronav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…Therefore there is a need to create expansive multivariate models that allow an algorithm’s prediction to incorporate patient risk profiles, with future studies developing a richer patient representation by incorporating features from EHRs and beyond. 56 In an early example of the potential of this technology, Isikli Esener et al 57 demonstrated that their novel proposed multistage classification scheme is more effective than the single-stage classification for computer-aided breast cancer diagnosis.…”
Section: Discussion: Challenges In Development and Adoption Of Machin...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore there is a need to create expansive multivariate models that allow an algorithm’s prediction to incorporate patient risk profiles, with future studies developing a richer patient representation by incorporating features from EHRs and beyond. 56 In an early example of the potential of this technology, Isikli Esener et al 57 demonstrated that their novel proposed multistage classification scheme is more effective than the single-stage classification for computer-aided breast cancer diagnosis.…”
Section: Discussion: Challenges In Development and Adoption Of Machin...mentioning
confidence: 99%
“…The technical aspects of model-building and computing power will continue to foster new decision-support solutions. 56 The future education of clinicians must cover aspects of AI that will allow them to appraise and appropriately use these new tools. 60 This understanding will also aid acceptance into practice and accelerate widespread clinical use.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%
“…In sum, the importance of building multi-modal network models has been discussed in the context of emerging field of network physiology (Bashan et al, 2012;Ivanov PCh, 2021) but also in the context of precision medicine and digital twins (Coorey et al, 2021;Björnsson et al, 2019;Lonsdale et al, 2022). Some promising and valuable computational models have been already developed in the field of human pain [see e.g., (Lang et al, 2021;Ionescu et al, 2019)] and a review of such models could help to understand, predict and analyze nociceptive system function and pain perception.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning is used increasingly for predicting outcomes in medicine 13 because it can compute complex nonlinear relationships across multiple variables and generate tailored recommendations for individual patients on a precision medicine basis. 14 We leveraged the APRICOT dataset with machine learning techniques to develop models that can determine which pediatric patients in ASA-PS class I-III are at low risk for severe perioperative critical events. We identified two time points in the clinical pathway at which individualized risk stratification would have utility.…”
Section: The Apricot (Anaesthesia Practice In Children Observationalmentioning
confidence: 99%